2013
DOI: 10.2214/ajr.12.9041
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of Critical Findings in Neuroradiology

Abstract: Compliance with reporting and communicating critical findings must be monitored. Calling clinicians to report noncritical findings may result in unnecessary interruptions in work flow for radiologists and referring health care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Whenever we discuss "labels" in this article, we are referring to these human-generated report annotations. In total, there were 55 labels included in the analysis, 20 of which were classified as critical labels on the basis of the criteria used at our hospital, which are derived from a previously published report (36). At our institution, reporting of acute ischemic stroke is required within 15 minutes of image acquisition, and reporting of intracranial hemorrhage, airway compromise, acute spinal cord compression, ruptured aneurysm, and markedly misplaced lines and tubes is mandated within 1 hour of image acquisition.…”
Section: Complexity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Whenever we discuss "labels" in this article, we are referring to these human-generated report annotations. In total, there were 55 labels included in the analysis, 20 of which were classified as critical labels on the basis of the criteria used at our hospital, which are derived from a previously published report (36). At our institution, reporting of acute ischemic stroke is required within 15 minutes of image acquisition, and reporting of intracranial hemorrhage, airway compromise, acute spinal cord compression, ruptured aneurysm, and markedly misplaced lines and tubes is mandated within 1 hour of image acquisition.…”
Section: Complexity Analysismentioning
confidence: 99%
“…two-dimensional visualizations in which the distance between points reflects their similarity in 400-dimensional space (37). clusters among learned word embeddings in the head CT corpus (36). We used t-distributed stochastic neighbor embedding (t-SNE) to generate (Fig 4).…”
Section: Modelingmentioning
confidence: 99%
“…A critical test result is defined as a finding that requires direct notification of a member of the patient's care team, including findings that could result in mortality or significant morbidity if appropriate steps are not undertaken [7]. In the United States, TJC trusts each hospital's leadership to approve and validate their own definition of critical test results [7,8]. In the Philippine General Hospital, no vetted critical radiology findings list or protocol for neuroradiology or cranial CT findings exists.…”
Section: Introductionmentioning
confidence: 99%
“…1 There have subsequently been protocols created to reach this goal, including those for the following: 1) defining a critical finding (CF), 2) communicating the critical finding to the physician, and 3) indicating what makes a report "timely." [2][3][4][5][6] TJC has never defined a CF, stating only "each organization can define for itself the circumstances under which a test result is considered 'critical.'" 1 The American College of Radiology identifies findings that require nonroutine communication as those "that suggest a need for immediate or urgent intervention."…”
mentioning
confidence: 99%
“…3,7 Another publication studied the existing list of critical findings in neuroradiology and revised that list to include frequent findings that were not previously identified in an effort to be more inclusive of lesions that warrant immediate communication. 4 Others have suggested that careful review of performance on an ongoing basis with regard to communication of radiologic critical findings can result in significant improvement in adherence to institutional guidelines.…”
mentioning
confidence: 99%